Genome analysis of the monoclonal marbled crayfish reveals genetic separation over a short evolutionary timescale - Maiakovska, Olena; Andriantsoa, Ranja; Tönges, Sina; Legrand, Carine; Gutekunst, Julian; Hanna, Katharina; Pârvulescu, Lucian; Novitsky, Roman; Weiperth, András; Sciberras, Arnold; Deidun, Alan; Ercoli, Fabio; et al. (Communications biology, 2021)
The marbled crayfish (Procambarus virginalis) represents a very recently evolved parthenogenetic freshwater crayfish species that has invaded diverse habitats in Europe and in Madagascar. However, population genetic analyses have been hindered by the homogeneous genetic structure of the population and the lack of suitable tools for data analysis. We have used whole-genome sequencing to characterize reference specimens from various known wild populations. In parallel, we established a whole-genome sequencing data analysis pipeline for the population genetic analysis of nearly monoclonal genomes. Our results provide evidence for systematic genetic differences between geographically separated populations and illustrate the emerging differentiation of the marbled crayfish genome. We also used mark-recapture population size estimation in combination with genetic data to model the growth pattern of marbled crayfish populations. Our findings uncover evolutionary dynamics in the marbled crayfish genome over a very short evolutionary timescale and identify the rapid growth of marbled crayfish populations as an important factor for ecological monitoring.